Anti-inflammatory properties of antidiabetic drugs: a “promised land” in the COVID-19 era? (2020)
Inflammation is implicated in the development and severity of the coronavirus disease 2019 (COVID-19), as well as in the pathophysiology of diabetes. Diabetes, especially when uncontrolled, is also recognized as an important risk factor for COVID-19 morbidity and mortality. Furthermore, certain inflammatory markers [i.e. C-reactive protein (CRP), interleukin6 (IL-6) and ferritin] were reported as strong predictors of worse outcomes in COVID-19 positive patients. The same biomarkers have been associated with poor glycemic control. Therefore, achieving euglycemia in patients with diabetes is even more important in the era of the COVID-19 pandemic. Based on the above, it is clinically interesting to elucidate whether antidiabetic drugs may reduce inflammation, thus possibly minimizing the risk for COVID-19 development and severity. The present narrative review discusses the potential anti-inflammatory properties of certain antidiabetic drugs (i.e. metformin, pioglitazone, sitagliptin, linagliptin, vildagliptin, alogliptin, saxagliptin, liraglutide, dulaglutide, exenatide, lixisenatide, semaglutide, empagliflozin, dapagliflozin, canagliflozin), with a focus on CRP, IL-6 and ferritin.